Applying A Multi-Criteria Decision Making (MCDM) Approach to Determine the Key Criteria for Taipei Creative City of Design (TCCD) As A Business Centre in Taiwan - Andi Sahputra Depari (Indonesian Journal of Business Analytics, 2021)
The aim of this research is to find out the key criteria for Taipei Creative City of Design (TCCD) as a business center in Taiwan according to the experts in terms of creative city of design. The methodology of this study consists of searching for the creative city of design indicators, which worked as alternatives for applying a multi-criteria decision making (MCDM), called the Analytic Hierarchy Process (AHP). Based on criteria derived from the literature, data collection and analysis that has been done, the researcher found that the human-oriented, design week/month, and city development are relatively high and should be given priority at the current stage. These results could provide a theoretical foundation for designing further the Taipei Creative City of Design.